Dampak Pandemi Covid-19 Terhadap Sosial Ekonomi Masyarakat Lokal Di Kawasan Pariwisata Desa Cihanjuang Rahayu (Studi Kasus: Daya Tarik Wisata Ciwangun Indah Camp) - Nirma Qurniani Kamelia; Jery Christianto; Irma Dela Larasita (Journal of Event, Travel and Tour Management, 2022)
The COVID-19 pandemic that has occurred throughout the world, including in Indonesia, has had a very significant negative impact on the development of the global and the national tourism sector, this is a consequence of the implementation of travel restrictions in many countries, including in Indonesia, such as large-scale social restrictions policies that the aim is to suppress the spread of COVID-19 during this pandemic. One of the focuses of tourism development developed by the government is tourism villages, but the number of visits to this tourism village is also affected by the COVID-19 pandemic. This research was conducted in Cihanjuang Rahayu Tourism Village, Parongpong District, West Bandung Regency, West Java Province where this village has the potential for developing agro-tourism, culinary tourism, cultural arts and nature tourism. The purpose of this study was to find out how the impact of the covid-19 pandemic on the number of visits and its implications for the economic conditions of the local community. The research method used is a qualitative approach, with primary data collection techniques, namely through field observations and interviews, as well as strengthening secondary data in the form of secondary data analysis. The results of this study are expected to have a positive influence on the management of tourism village in Cihanjuang Rahayu, especially after the Covid-19 pandemic so that tourism activities can continue to be sustainable and provide benefits to the community, especially in efforts to improve the local community's economy. Keywords: The Effect of the Covid-19 Pandemic, Tourism Villages, Economy, Local Communities